Applying NEM to Pulau Redang - Abd Razak, Dzulkifli (2010)
TURNING Pulau Redang in Trengganu into a fivestar destination might not be a bad idea to attract highend tourists to Malaysia. Last year we chalked up a good number to our shores, and this island resort could be a new magnet for the exotic East. But we can also learn a thing or two from another popular favourite island resort, Pulau Pinang, once known as the Pearl of the Orient. Now it seems its pearly lustre is gone. Some tourists have sworn not to return unless something is done about it.